Molecular epidemiology of unrelated clusters of multiresistant strains of Haemophilus influenzae. - Dimopoulou, I; Kraak, W; Anderson, E; Nichols, W; Slack, M; Crook, D (1992)
Three epidemiologically unrelated clusters of Haemophilus influenzae resistant to ampicillin, chloramphenicol, and tetracycline were studied. The biotypes and cell-envelope protein patterns were determined for 17 nonencapsulated strains, 6 from Dundee and 11 from Cheltenham, and for 6 type b encapsulated strains from Guildford. After mobilization by conjugation, large 32- to 36-MDa plasmids were purified from all the strains. The restriction fragment patterns of the plasmids were determined by ethidium bromide staining of digested purified plasmid or by Southern hybridization of digested total cellular DNA of the parent strains, probed with purified plasmid. Evidence is presented for a chromosomal location of the plasmids in the parent strains, the spread in nature of a plasmid between distinguishable strains of H. influenzae, the person-to-person spread of a strain within a cluster, and a high degree of sequence homology between distinguishable plasmids, implying their close relatedness.